Beamforming for SC-FDMA transmission over MIMO ISI channels with decision-feedback equalization - Dang, Thi Uyen Ly; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2010 International ITG Workshop on Smart Antennas (WSA), 2010)
We consider transmit beamforming algorithms for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filters are designed for optimum performance of MIMO minimum mean-squared error decision-feedback equalization (MMSE-DFE). It turns out that eigenbeamforming diagonalizing the overall channel is optimum, and in addition an optimum power allocation has to be performed which is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Yang and Roy. Simulation results indicate that the proposed solution is beneficial for the block error rate performance of an SC-FDMA transmission scheme with strong channel coding and error-free decisions in the feedback path of MMSE-DFE, which can be guaranteed e.g. by equivalent Tomlinson-Harashima precoding at the transmitter sid

Efficient receivers for GSM MUROS downlink transmission - Meyer, Raimund; Gerstacker, Wolfgang; Obernosterer, Frank; Ruder, Michael; Schober, Robert (2009 IEEE 20th International Symposium on Personal, Indoor and Mobile Radio Communications, 2010)
Currently, Multiple Users Reusing One Slot (MUROS) is discussed in 3GPP GERAN as an extension of the GSM standard. In MUROS, two overlaid GMSK signals are transmitted in the same time slot and at the same frequency resource. By this, capacity of existing GSM networks in principle can be doubled and up to four half rate voice users can share one time slot. In this paper, channel estimation and detection is investigated for the MUROS downlink. Two novel channel estimation algorithms are presented, taking into account the specifics of the MUROS downlink. For detection, a joint MLSE of both user signals can be applied in case of noise limited scenarios. For interference limited environments, it turns out that approaches based on the mono interference cancellation (MIC) algorithm for single antenna interference cancellation (SAIC) are more favorable. It is shown that the standard MIC algorithm performs sufficiently well and could be used for a fast introduction of MUROS in existing GSM networks. For enhanced performance, a novel algorithm based on MIC along with successive interference cancellation is proposed. The presented results demonstrate that an even better performance as the GSM reference performance before introduction of SAIC can be obtained for MUROS if well-designed receivers are use

GSM/EDGE: A mobile communications system determined to stay - Gerstacker, Wolfgang; Schober, Robert; Meyer, Raimund; Obernosterer, Frank; Ruder, Michael; Kalveram, Hans (AEÜ - International Journal of Electronics and Communications, 2011)
The Global System for Mobile Communications (GSM) is still the most successful mobile communications system worldwide. During the last decade, major steps have been taken towards an improvement of GSM with respect to performance and spectral efficiency. To serve the increasing demands of more and more users for higher data rates, significant efforts are made towards a further evolution of GSM. The standard extension Voice Services over Adaptive Multi-User Channels (VAMOS) has been specified in 3GPP Release 9. In VAMOS mode, two overlaid Gaussian minimum-shift keying (GMSK) signals are transmitted in the same time slot and frequency channel, potentially doubling the capacity of existing GSM networks in many cases. In this paper, we address channel estimation and detection techniques for the VAMOS downlink. In a new 3GPP work item called TIGHTER, it is also foreseen to tighten all downlink receiver performance requirements for all data and voice services by at least 2 dB through the application of more sophisticated processing techniques at the receiver. Furthermore, a 3GPP study on Signal Precoding Enhancements for EGPRS2 (SPEED) to further modify the modulation and coding for data services by introducing OFDM has been started recently. We present ideas for improved receivers to enable tighter performance requirements and for SPEED transmission concepts, which might merit further investigation. © 2011 Elsevier GmbH. All rights reserved.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Decoding; Equalization; GSM/EDGE; OFDM; SAIC; VAMOS

Joint user pairing, frequency allocation, and beamforming for MIMO SC-FDMA transmission with QoS requirements - Ruder, Michael; Gerstacker, Wolfgang (2014 IEEE Wireless Communications and Networking Conference (WCNC), 2014)
In this paper, we consider joint user pairing and frequency allocation with beamforming (BF) assuming per user Quality of Service (QoS) requirements. A single-carrier frequency-division multiple-access (SC-FDMA) transmission employing a zero-forcing (ZF) detector at the receiver is assumed. The BF filter coefficients are jointly optimized with the user pairing and frequency allocation of the users. The transmit power savings achievable by combining BF with user pairing and frequency allocation are compared to these of a constant power allocation over all subcarriers. To this end, BF filter coefficient optimization and constant power allocation are briefly revisited and novel BF filter solutions for single-input multiple-output (SIMO) and single-input single-output (SISO) transmission, respectively, are derived for SC-FDMA. Numerical results show that the transmit power can be significantly reduced with BF for suboptimum algorithms, but for optimal joint user pairing and frequency allocation the gain of BF compared to constant power allocation is negligibl

MMSE beamforming for SC-FDMA transmission over MIMO ISI channels - Dang, Uyen Ly; Ruder, Michael; Schober, Robert; Gerstacker, Wolfgang (EURASIP Journal on Advances in Signal Processing, 2011)
We consider transmit beamforming for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filters are optimized for minimization of the sum of the mean-squared errors (MSEs) of the transmitted data streams after MIMO minimum mean-squared error linear equalization (MMSE-LE), and for minimization of the product of the MSEs after MIMO MMSE decision-feedback equalization (MMSE-DFE), respectively. We prove that for SC-FDMA transmission in both cases eigenbeamforming, diagonalizing the overall channel, together with a nonuniform power distribution is the optimum beamforming strategy. The optimum power allocation derived for MMSE-LE is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Berger/Tufts and Yang/Roy, whereas for MMSE-DFE the capacity achieving waterfilling strategy well known from conventional single-carrier transmission schemes is obtained. Moreover, we present a modification of the beamformer design to mitigate an increase of the peak-to-average power ratio (PAPR) which is in general associated with beamforming. Simulation results demonstrate the high performance of the proposed beamforming algorithms. Copyright © 2011 Uyen Ly Dang et al.
CRIS-Team Scopus Importer:2020-02-03

MMSE Beamforming for SC-FDMA Transmission over MIMO ISI Channels with Linear Equalization - Dang, Thi Uyen Ly; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2011)
We consider transmit beamforming for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filter is optimized for minimization of the sum of the mean-squared errors (MMSEs) of the transmitted data streams after equalization. Here, MIMO minimum mean-squared error linear equalization (MMSE-LE) is considered. We prove that for SC-FDMA transmission eigen-beamforming diagonalizing the overall channel together with a nonuniform power distribution is the optimum beamforming strategy in the MMSE sense. The derived optimum power allocation is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Berger/Tufts and Yang/Roy. Moreover, we present a modification of the beamformer design to mitigate an increase of the peak-to-average power ratio (PAPR) which is in general associated with beamforming. Simulation results demonstrate the excellent performance of the proposed beamforming algorith

Multiuser MIMO Empfänger für den Uplink von Long Term Evolution (LTE) - Ruder, Michael (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2008)

Single-antenna interference cancellation for complex-valued signal constellations with applications to GSM/EDGE - Lehmann, Andreas; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2011 IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications, 2012)
Different approaches for single antenna interference cancellation (SAIC) in GSM/EDGE have been proposed. Most of them work best in synchronous interference environments. We propose three different modifications of the conventional EDGE receiver, which target the harmful effects of asynchronous co-channel interference (ACCI). All modifications are applicable to all linear modulation alphabets and do not require any modification of the GSM/EDGE air interface. We model the effect of ACCI as impulsive Generalized Gaussian noise. The proposed methods include a modification of the conventional path metrics for the reduced-state equalizer and the decoder, respectively, as well as a Viterbi algorithm, which performs erasure decoding. Based on simulation results, the performances of the proposed schemes are compared with that of a standard GSM/EDGE receiver. We show that all three proposed schemes outperform the standard receiver in ACCI environments and discuss their complexit

Single Antenna Interference Cancellation for GSM/VAMOS/EDGE Using Lp-Norm Detection and Decoding - Ruder, Michael; Lehmann, Andreas; Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Wireless Communications, 2015)
Different schemes for single antenna interference cancellation (SAIC) in the Global System for Mobile Communications (GSM) have been proposed so far. Most of these schemes work best in synchronous interference environments and are limited to Gaussian minimum-shift keying (GMSK) modulation. In this paper, we propose several modifications of the conventional GSM receiver, which target the harmful effects of asynchronous co-channel interference (ACCI). Based on the observation that the impairment caused by ACCI cannot be modeled as additive Gaussian noise, which was assumed for the derivation of the metric used in state-of-the-art receivers, we propose modeling the impairment as Generalized Gaussian noise (GGN). This leads to modifications of the conventional branch metrics of the reduced-state equalizer and the decoder employed at the receiver. Both proposed modifications are applicable to any linear modulation alphabet and do not require any modification of the GSM air interface. Hence, the proposed novel branch metrics are also applicable in Enhanced Data Rates for GSM Evolution (EDGE) systems which employ 8-ary phase-shift keying (8-PSK) modulation and where the SAIC algorithms tailored for GMSK cannot be used. Furthermore, we show that the proposed branch metric modifications also improve the performance of the new Voice Services over Adaptive Multiuser channels on One Slot (VAMOS) extension of GSM in ACCI environments. Based on simulation results, the performance of the proposed schemes is compared with that of an unmodified receiver employing the conventional Gaussian metric. We show that the proposed receivers outperform the unmodified receiver in ACCI environments and discuss the complexity entailed by the proposed branch metric modifications.<br
Keywords: Measurement; GSM; Receivers; Decoding; Equalizers; Interference; Modulation

Turbo-Interferenzreduktion für Einträgersysteme - Ruder, Michael (2007)

User Pairing for Multiuser SC-FDMA Transmission over Virtual MIMO ISI Channels - Ruder, Michael; Dang, Thi Uyen Ly; Gerstacker, Wolfgang (GLOBECOM 2009 - 2009 IEEE Global Telecommunications Conference, 2010)
This paper proposes different criteria for user pairing for a virtual multiple-input multiple-output (V-MIMO) single-carrier frequency-division multiple access (SC-FDMA) transmission over intersymbol interference (ISI) channels. Two users, equipped with a single antenna each, transmit their data in the same time slot and frequency band. The receiver at the base station (BS) is assumed to have two antennas and separates both users with a multiuser equalizer. For this, linear minimum mean-squared error (MMSE) equalization and successive interference cancellation (SIC), respectively, are chosen. Various pairing criteria are proposed and compared by simulations for a transmission in the uplink of E-UTRA Long Term Evolution (LTE). The simulation results indicate that well-designed user pairing strategies yield significant gains compared to random user pairing. It is shown that the proposed novel bit error rate (BER) pairing achieves a significant performance gain compared to capacity pairing for a SIC receiver and higher order modulatio